Pengaruh Brand Image, Presepsi Harga, Dan Promosi Terhadap Keputusan Pembelian Produk Mie Gacoan Di Wilayah Solo - Restu Putri Permatasari; Oktafianis Oktafianis; Rayhan Gunaningrat (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to determine the influence of brand image, price perception, and promotion on the purchasing decisions of Mie Gacoan products in the Solo region. The study utilizes a quantitative approach, employing primary data obtained through distributing written instruments or questionnaires and receiving responses from 100 samples. Smart PLS (Partial Least Square) analysis is used to evaluate the hypotheses in this research, which is a quantitative approach. Based on the results of the Smart PLS analysis conducted, it shows that purchasing decisions are positively (significantly) influenced by brand image, price perception, and promotion.